2018
DOI: 10.3126/jsan.v4i2.21206
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine with Midazolam and Ketamine alone as oral premedication in children: a randomized trial

Abstract: Background: Fear of operation, injections, physicians and peculiar operation theatre environment where children are separated from their parents prior to anesthesia invariably produce traumatic experiences in tender mind of young children. Midazolam and Ketamine are useful for oral premedication in children to allay anxiety, allow separation from parents and to ensure smooth induction.Methodology: It was a prospective, randomized, double-blinded and comparative study conducted in 80 children of ASA I and II ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The study done by Thakur JP et al [13] also showed almost similar results comparable to our study. [6] .…”
Section: Discussionsupporting
confidence: 92%
“…The study done by Thakur JP et al [13] also showed almost similar results comparable to our study. [6] .…”
Section: Discussionsupporting
confidence: 92%
“…Sample size was calculated based on 95% confidence interval ( α = 5%) and 80% power ( β = 10%) and a sampling formula [ 15 ]: n = (2 × ( Zα + Z β ) 2 × SD 2 )/ d 2 , where Zα = 1.96, Zβ = 1.28 [ 16 ]. The size of CP was the main variable of interest, 22.5 was the SD of CP size percent detected in the previous experiment, and 10% was postulated as a clinically significant difference in CP size between the two groups (d).…”
Section: Methodsmentioning
confidence: 99%